HUBUNGAN DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP LANSIA DI KELURAHAN TURIDA, KECAMATAN SANDUBAYA, KOTA MATARAM - Dinda Amalia Shaleha; Dany Karmila; Velia Maya Samodra; Dasti Anditiarina (Yayasan Nusantara Hasana Berdikari, 2023)
The elderly is someone who has reached the age of 60 years and over. United Nation data for 2021 shows that there are 13,7% of the world’s elderly population and Indonesia ranks 8th. One of the provinces in Indonesia, namely NTB, ranks 18th with the highest number of elderly people in 2022. The aging process in elders results in physiological changes in the body, from physical to psychosocial changes that affect their quality of life. Family support is an important factor in improving the quality of life of the elderly. This study aims to determine the relationship between family support to the quality of life of the elderly in Turida Village, Sandubaya District, Mataram City. The research design is a cross-sectional study of a measuring instrument a questionnaire. The research sample was 100 elderly respondents using a purposive sampling technique. The research was conducted in Turida Village, Sandubaya District, Mataram City. The bivariate analysis test used the Spearman rank correlation test. The results of this study were respondents who had good family support with a high quality of life were 58 people (61,7%) and a low quality of life (0,0%). Respondents who had sufficient family support with a high quality of life were 36 people (38,3%) and a low quality of life was 1 person (16,7%). Respondents who lack family support with a high quality of life (0,0%) and a low quality of life were 5 people (83,3%). The results of the analysis using the Spearman rank correlation test, show that the p-value = 0.001 (p-value <0.05) and a value of r = 0.443. There is a significant relationship between family support on the quality of life of the elderly in Turida Village. The results of the r value are moderate and positive, and the direction of the correlation is unidirectional, meaning that the greater the value of one variable, the greater the value of the other variables.